Analysis of clinical characteristics of the obstetric patients admitted to intensive care unit at a tertiary care institute - Bhugra, Parul; Dahiya, Pushpa; Duhan, Nirmala; Singhal, Savita Rani; Chauhan, Meenakshi Barsaul (Asian Journal of Medical Sciences, 2025)
Background: Pregnancy and puerperium usually progress uneventfully but may get complicated requiring admission to the intensive care unit (ICU). The obstetric patients admitted to ICU have been reported to have higher mortality in comparison with non-obstetric patients. Aims and Objectives: The study was conducted to identify the risk factors and diseases associated with maternal ICU admissions and to find out the case fatality rate (CFR). Materials and Methods: One hundred and forty maternal patients who required ICU admission at a tertiary care hospital were retrospectively analyzed. Results: The mean age of the patients was 24.71 years. About 81.43% patients were antenatal, 17.14% were postnatal while 1.43% patients were postabortal. The risk factors for the admission to ICU were younger age, rural background, lower socio-economic status, and last trimester of pregnancy. The obstetric indications for ICU admissions were hypertensive disorders of pregnancy (54.28%), obstetric hemorrhage (12.86%), peripartum cardiomyopathy (2.86%), and septic abortion (0.71%). The common non-obstetric indications for ICU admissions were pre-existing cardiac diseases and severe anemia (7.86% each) and pulmonary edema (3.57%). Maternal mortality was observed in 32.09% patients. The non-obstetric causes were found to have higher CFR (59.46%) than obstetric causes (21.65%) of maternal ICU admission. Conclusion: Early identification of the patients at risk for ICU admission and timely care of these patients is likely to reduce the maternal ICU admissions. The causes associated with higher case fatality particularly require dedicated ICU care.